2012
DOI: 10.1097/phm.0b013e318269d748
|View full text |Cite
|
Sign up to set email alerts
|

Using Lean Principles to Manage Throughput on an Inpatient Rehabilitation Unit

Abstract: Performance improvement is a mainstay of operations management and maintenance of certification. In this study at a University Hospital inpatient rehabilitation unit, Lean management techniques were used to manage throughput of patients into and out of the inpatient rehabilitation unit. At the start of this process, the average admission time to the rehabilitation unit was 5:00 p.m., with a median time of 3:30 p.m., and no patients received therapy on the day of admission. Within 8 mos, the mean admission time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Lean management tools and techniques have many process management applications as regards health care and organizations that can improve quality, patient safety and cost-effectiveness (27;28). These tools and techniques need to be related to the overall strategy and the principles of Lean health care to be successful (8).…”
mentioning
confidence: 99%
“…Lean management tools and techniques have many process management applications as regards health care and organizations that can improve quality, patient safety and cost-effectiveness (27;28). These tools and techniques need to be related to the overall strategy and the principles of Lean health care to be successful (8).…”
mentioning
confidence: 99%
“…Hospital staff should be aware of the errors that occur in the department. They can easily ask the individuals at higher levels about the decisions and actions of the department just in case and also can freely speak on issues that may have a negative impact on the patient care (35).Concerning the dimension "teamwork across units", the highest mean ranking was influenced by the term "It was often unpleasant to work with the staff from other hospital units".…”
Section: Discussionmentioning
confidence: 99%
“…These included small, single-institution studies with universal improvement on targeted process measures, improvement on some outcome measures, self-reported increases in QI engagement and application, or improvements in knowledge. [99][100][101][102][103][104][105][106][107] However, one local study of inpatient pediatricians showed that improvements made in body mass index documentation were not sustained after the intervention. 108 Small, single-institution QI interventions designed to meet both ACGME and practice improvement (Part IV) MOC requirements demonstrated universal improvement on targeted process measures reflecting the care delivered by trainees.…”
Section: Moc Practice Improvement Activities (Part Iv)mentioning
confidence: 99%